Pemanfaatan Automatic Switch Kontrol Dengan Memanfaatkan Jaringan Internet Of Things (IoT) Di Universitas Nurul Jadid - M. Fadhilur Rahman; Aprlian Diki Setiawan; Mohammd Roviq (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
In this mini service project, the focus partner is a private university, namely Nurul Jadid University. The problem faced by partners is that the process of controlling the production equipment used at Nurul Jadid University is still manual, causing less than optimal efficiency and a fairly high error rate. The form of service that will be carried out is by implementing an Automatic Switch Control system using Internet of Things (IoT) technology at Nurul Jadid University. This system will replace manual processes with automation methods that can monitor the condition of production equipment and control it in real time. The proposed solution will involve installing sensors connected to an IoT (Internet Of Things) network on each production equipment. Data from these sensors will be sent to the control center which will control the Automatic Switch to regulate and monitor equipment performance in real-time.